AKT-like como parte de las rutas de señalización de la supervivencia celular de Trypanosoma cruzi y Trypanosoma brucei - Díez-Mejía, Andrés Felipe; Varela-Miranda, Rubén Eduardo; Pulido-Muñoz, Sergio Andrés; Echeverry-Gaitán, María Clara; Marín-Villa, Marcel (Iatreia, 2019)
-